Planning of Supervision of Madrasah Principals on the Performance of Educational Personnel in Madrasahs - Ramdhani, Deden; Robbi, Mochammad Maulana (UII Darullughah Waddawah Pasuruan, 2024)
Education is a vital component in the development of a nation, and the quality of education is greatly influenced by the management of human resources for education personnel. To improve the professionalism of education personnel, human resource management in education needs to be improved and monitored regularly. This study aims to analyze the planning and implementation of the madrasah principal's supervision, with the goal of improving the performance of education personnel at MTsN 1 Pasuruan. The research method used is a case study with a qualitative approach. Data collection techniques include observation, interviews, documentation, and triangulation, while data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the planning of supervision by the madrasah principal follows the stages that have been set out in the supervision book, such as background and legal basis, results of previous year's supervision, setting targets and schedules, selecting appropriate approaches, techniques, and models, and selecting supervision instruments. In its implementation, supervision is carried out in a family manner, which allows education personnel to feel appreciated and actively involved in the education process without feeling forced. The contribution of this study shows that effective supervision can improve the performance and professionalism of educational staff, which in turn improves the quality of educational services in institutions. Fulfillment of educational staff competencies is an important factor in achieving these goals.